IMPACT OF THE POLICY OF THE COVID-19 PANDEMIC ON STUDENTS' UKT INCOME - Andriana, Budi; farinduanti, Aulia; Mujayanah, Mujayanah; Anggono, Puspo; Andriansyah, Eka Hendi (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This research was prepared with the aim of knowing the effectiveness of the implementation of UKT adjustment policies and how they impacted the finances of Higher Education Institutions. The study used a descriptive approach with the use of primary data from student responses and secondary data from financial reports published by Unesa. The results that can be found in this study include the Higher Education Policy in terms of the effective implementation of UKT money adjustments. Based on the indicators of the effectiveness of the policy, the four indicators are the right policy, the right implementation, the right target and the environment as a whole. This can be seen from the student's response which has an impact on their mentality in the spirit of students continuing to carry out lectures and there is no dropout or late graduation in 2020. Higher education policies in terms of adjusting UKT money include adjusting UKT because the impact of the covid-19 pandemic has an effect on decreasing The University's Non-Tax National Income (PNBP) is 13%. However, the decrease in income was offset by a decrease in higher education operational costs as a form of efficiency that has been carried out by Unesa, which was 26%, so that the level of higher education financial deficit did not increase and did not interfere with higher education services to the academic community